JMC462 : Computer aided design 1 / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
The course is designed to help students to learn dimensioning, designing and rendering using 3 Dimensional software. Students will be equipped with the skills to solve drawing problems and execute drawings using drafting and design software. Students will also be introduced to isometric, 3D drawing and rendering in various scenes.